Participation of a Lanna Community in the Administration of Basic Education: A Case Study of Ban Pakoi Community, Chiang Saen District, Chiang Rai Province - Suphakat, Thanaset; Buawsuwan, Prompilai; Wichitputchraporn, Wisut; Xuto, Nisa (Kasetsart Journal of Social Sciences, 2014)
The purposes of this research were: 1) to study the way of life and participation process of a Lanna community in the administration of basic school education and 2) to develop guidelines for community participation in basic school education that is suitable for the way of life of a Lanna community. Qualitative research methodology was employed to gain an understanding of community participation. The Ban Pakoi community located in Chiang Saen district, Chiang Rai province was purposively chosen as a site for the study. Observations, in-depth interviews, and focus group discussions were used as methods of data collection. Key informants included community leaders, teachers, school board members, and parents in the Ban Pakoi community. Data were analyzed using data interpretation, data reduction, coding, categorizing, grouping into themes, and finding relationships to propose guidelines for community participation. The findings of this research revealed that the Lanna way of life affected the community participation process in school administration. The relationships among community leaders, religious groups, and school members played significant roles in school-community participation. The socio-economic conditions of the community also affected the characteristics of participation and the extent to which community members participated in school administration. This study, therefore, proposed guidelines for building Lanna community participation in school administration based on role and function analysis of the school and community members. Community leaders should play roles in school decision-making and planning. Teachers, school board members, and students should play roles in the coordination and implementation. Finally, parents and other community members should support school activities.